Supplementation of Quercetin Nutraceutical Ameliorates Stress among Female College Students: Life Sciences-Physiology - Mitra, Sudeep; Mitra, Mousumi; Saha, Mantu; Nandi, Dilip Kumar (International Journal of Life Science and Pharma Research, 2022)
Restricted information regarding the protective effect of quercetin against stress-effectuated depression, anxiety and hypertension in students has been evaluated. Quercetin, king of flavonoids offers a great promise to reduce depression that negatively affects human mental and physical health which ultimately proliferates cardiovascular risks. This study aimed to enlighten the propitious effect of oral consumption of quercetin at a dose of 200 mg/day for 30 days on healthy college students prone to academic stress to explore its beneficial effects on body composition, blood pressure, oxidative stress and inflammatory markers in a randomised, double-blinded, placebo-controlled cross-over trial (n=100). In contrast to placebo, quercetin-rich supplementation significantly reduced (p‹0.05) psychological stress scale, body fat ratio (BFR), pulse rate, systolic pressure (SP) and tumour necrosis factor-alpha (TNFα) from their baseline values. Furthermore, a significant increase (p‹0.05) in oxidative and (anti) inflammatory marker i.e., superoxide dismutase (SOD) and interleukin 10 (IL10) were observed but did not affect catalase (CAT) and reduced glutathione (GSH) when compared with placebo. Thus, daily quercetin-rich supplementation supervenes antidepressant effects by attenuating inflammatory response, rehabilitating the activity of antioxidant enzymes, declining oxidative stress markers and hence improving alterations of the HPA axis which ultimately reduces blood pressure. These data are the first to our knowledge to show that quercetin supplementation could be a supportive therapy for improving stress and physical fitness in depressed subjects. This indicates the effectiveness of the flavonoid as a nutraceutical compound against the expansion of behavioural perturbation induced by psychological stress in a cost-effective, biofriendly manner. We explored a non-pharmacological but decent supra nutritional dose of quercetin since these data should provide a rational basis for the development of functional foods. The interminable effectiveness of quercetin supplementation for better improvement of stress remains to be investigated.